Multisystem inflammatory syndrome in adults (MIS-A) following COVID-19 requiring venoarterial extracorporeal membrane oxygenation. Issue 3 (7th March 2022) - Newman, Seth; Zou, Fengwei; Madan, Shivank; Sims, Daniel
Abstract : The SARS-CoV-2 virus has caused a global pandemic with serious impact around the world. Patients most commonly present with severe lung involvement and acute respiratory failure; however, multisystem inflammatory syndrome in adults (MIS-A) is a known—although rare—complication. We present a case of a 49-year-old patient who presented with combined cardiogenic and vasodilatory shock and was diagnosed with MIS-A. He initially required venoarterial extracorporeal membrane oxygenation and Impella for haemodynamic support but was able to be weaned off these devices with complete recovery of left ventricular systolic function. This case demonstrates that MIS-A may present as haemodynamic collapse in adults, but complete recovery is possible with proper haemodynamic support.